Regional Geological Data on the Volturno Basin Filling and Its Relationship to the Massico Structure (Southern Tyrrhenian Sea, Italy) - Gemma Aiello (Journal of Marine Science and Engineering)
We built a regional geological section founded upon the assessment of a seismic line in the Volturno basin, which is situated on the northern Campania continental shelf of the Tyrrhenian margin of Southern Italy. This section has been integrated with multichannel seismic data of Zone E (ViDEPI project) to highlight its relationships with the Massico structure. In the Volturno basin, there are four Pleistocene to Holocene units, recognized based on seismic analysis lie above deep seismo-stratigraphic units, related to Campania Latium carbonate platform and The Frosinone Flysch. Onshore and offshore seismic data, calibrated with lithostratigraphic correlation, have displayed the seismo-stratigraphic framework, including both sedimentary and volcanic seismo-stratigraphic units. Of these, the lavas associated with the Northern Campania Volcanic Zone’s Villa Literno volcano are associated with seismic unit 2a. Seismo-stratigraphic data has shown the offshore prolongation of the Massico structure, as involved by normal faults and flower structures. The whole-data interpretation suggests that the tectonic activity acted in correspondence to normal faults, which have controlled half-graben and interposed structural highs, fitting to the regional geological setting of the continental margin.